The Effectiveness of Brand Personality & Affective Commitment in Capturing Brand Loyalty: A Study of Retailers in UK - Muhammad Abu Huraira; Usman Ahmad (iRASD Journal of Management)
Marketing research theorists have concentrated their focus in studying the emblematic meaning consumers attach to certain brands. One such concept is brand personality. The brand personality scale proposed by Aaker is popular tool for the measurement of different product categories however, its application on retailers has been a rarity. Moreover, researchers have also called for adopting a multi-dimensional approach towards the study of brand loyalty which includes loyalty dimensions of both behavioral and attitudinal loyalty in conjunction with the brand personality concept. The specific objective of this study is to assess the effectiveness brand personality in capturing consumers’ loyalty towards a retailer. Stratified random sampling was applied for gathering the data from 120 consumers belonging to the three retailers in UK. The results showed a direct influence of brand personality on dimensions of loyalty. In addition, the three retailers were found to have different brand personality dimensions. The study suggests that managers should work towards building a retail brand personality to influence the loyalty of consumers. The scope of this study can be further widened by investigating ways of building a brand personality for retailers. The results of this study have contributed to the area of retail branding in a way that this research is performed in a different setting.